2016
DOI: 10.2494/photopolymer.29.547
|View full text |Cite
|
Sign up to set email alerts
|

Semitransparent Inverted Organic Solar Cells Using an Oxide/metal/oxide Transparent Anode

Abstract: Semitransparent inverted bulk-heterojunction solar cells were fabricated on an ITO/glass substrate utilizing oxide/metal/oxide transparent anode. The device structure was glass/ITO/PFN/PTB7:PC 71 BM/MoO 3 /Au/MoO 3 . The semitransparent solar cell showed a transparency of 44% at 550 nm and bifacial power generation at both front and backside illumination. The power conversion efficiencies (PCEs) with light illuminated from ITO or Au/MoO 3 side were 2.8% and 2.3%, respectively. Fabrication of stacking structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…5(a). In this case, the 10 nm-thick MoO 3 layer was used as a buffer layer, whereas the 20 nm-thick top capping MoO 3 layer was deposited to enhance transmittance in the visible region [12]. A photograph of the cell is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…5(a). In this case, the 10 nm-thick MoO 3 layer was used as a buffer layer, whereas the 20 nm-thick top capping MoO 3 layer was deposited to enhance transmittance in the visible region [12]. A photograph of the cell is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1(a). The fabrication process employed herein is based on our previously reported method [12] using the following procedures.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As the active area increases to 2.25 cm 2 , the PCE of the ZAZ top electrode-based devices decreased to 2%, while the devices based on ITO top electrode exhibited a PCE of only 1.5%, which is 30% lower than ZAZ cells. Fujii et al [77] reported semitransparent inverted bulk heterojunction solar cells, utilizing MoO 3 / Au/MoO 3 transparent anode, in which the thickness of Au was 15 nm and MoO 3 layers sandwiching the Au film were 10 nm. The device structure is glass/ITO/PFN/PTB7:PC 71 BM/MoO 3 / Au/MoO 3 .…”
Section: Metal Oxide-involved Multilayer Ttementioning
confidence: 99%